SMKS X Sidoarjo Inventory: Website-Based Facility Information System: Inventarisasi SMKS X Sidoarjo : Sistem Informasi Sarana Berbasis Website - Tubira, Muchamad Firmansyah; Suprianto (Procedia of Engineering and Life Science, 2024)
SMK X Sidoarjo is an educational institution that has received support from the Education Office as an Industrial Revolution 4.0 school. SMK X Sidoarjo needs to take advantage of technological advances. School infrastructure is very important for the process of education, monitoring and effective inventory management. Therefore, researchers built an information system "Inventory of Goods" that can be accessed via the internet for school infrastructure. This research method uses the System Development Life Cycle (SDLC) waterfall model approach to build a web-based "Item Inventory" information system. SMK X Sidoarjo requires further information system improvements along with the development of institutions and the need for more sophisticated inventory management, so that input and storage are no longer carried out manually so that decision making can be done quickly and accurately. The program has achieved success by implementing a web-based "Item Inventory" Information System in schools. The result is that the implementation of this system has improved the efficiency, transparency, and effectiveness of overall inventory management.